Infrared Thermography – A Novel Tool in the Surgical Treatment of H3 K27M-Altered Diffuse Midline Spinal Cord Glioma: Technical and Case Report - Quiuqui, Gabriel Filipe Soares; Diniz, Bárbara Moreira; Duarte, Antonio Augusto de Carvalho; Castro, Caio Cesar Martins Pedrosa de; Souza, Daniel Mendes de; Sampaio, Artiel Aurino Sousa; Oliveira, Lucas Scharf; Souza, Lucas Rodrigues de; Freitas, Marcelo Mamede de; Henriques, Leonardo Augusto Wendling (Brazilian Journal of Oncology, 2025)
Diffuse midline gliomas (DMGs), H3K27-altered, are rare and aggressive tumors primarily affecting children, though adult cases occur. These gliomas present significant surgical challenges, and novel techniques are needed to improve outcomes. We present the case of a 53-year-old male with a solid expansive lesion located at T12 to L1, who presented with bilateral thigh pain, loss of sphincter control, and increased urinary frequency. Initial magnetic resonance imaging suggested an ependymoma; however, tumor resection followed by immunohistochemical analysis confirmed a diagnosis of diffuse midline glioma, H3K27-altered. The patient underwent a successful two-level lumbar laminectomy with a microsurgical gross total resection. An innovative technique of intraoperative infrared thermography mapping was employed, representing a novel approach for this rare tumor. The patient remains alive at the time of the present publication.
Keywords: glioma; thermography; surgical oncology; spinal cord neoplasms